Lymphatic Vessel Memory Stimulated by Recurrent Inflammation - Kelley, Philip M. (American Society for Investigative Pathology, 2013)
Inflammation stimulates new lymphatic vessel growth (inflammatory lymphangiogenesis). One key question is how recurrent inflammation, a common clinical condition, regulates lymphatic vessel remodeling. We show here that recurrent inflammation accelerated the development a functional lymphatic vessel network. This observation suggests a novel program of lymphangiogenesis and identifies a property of lymphatic vessel memory in response to recurrent inflammation. A brief episode of initial inflammation regressed lymphatic vessels, and a significant increase in CD11b(+) macrophages were associated with the development of lymphatic vessel memory. These vessels had major differences in the structure and the spatial distribution of specialized lymphatic vessel features. Surprisingly, we found that the lymphatic vessel memory response did not depend on the vascular endothelial growth factor C or A pathway, indicating that different molecular pathways regulate inflammatory lymphangiogenesis and lymphatic vessel memory. These findings uncover a priming mechanism to facilitate a rapid lymphatic vessel memory response: a potential important component of peripheral host defense.